#TITLE_ALTERNATIVE# - ANDIKA CANDRA (NIM : 123 08 029), SAPTO
Interpretation of faults in seismic data is today a time consuming manual task. A new method for automatic extraction of fault surfaces from consolidated fault enhancing attributes is presented. Method used here is ant track method. This method is describing the collective behaviour that emerges from a group of social insects. An example is how ants find the shortest path between the nest and a food source by communicating vie pheromone, a chemical substance that attracks other ants. For the whole step of fault and fracture delineation, we have three main steps: seismic conditioning, edge enhancement using variance attribute, and the last step is ant track filter. For the result of this research, we will get the best parameters for each step : for seismic conditioning, we have inline 3, crossline 3, and vertical scale 1. For variance attribute, the best parameters are 3-3 for the inline and crossline range. And the last, for ant track filter, we are proposed to use passive ant track. Ant track helps to delineate the fault and fractures visualization for the spatial discontinuity, as predicted as fractures and faults. Sapta field has major fault's orientation as azimuth : 330 NW - 30 NE ; 150 SE - 205 SW and dip : 30° - 90°.